Evaluating Basic Education in Singapore: Trends and Dynamics - Helen Ngozi Elems-Ikwegbu (Jurnal Syntax Admiration, 2023)
This paper set out to evaluate the trends and dynamics of basic education in Singapore. It explored the country's emphasis on refined learning system in primary and secondary schools, efficient human resources policies, and state-of-the-art tools. This study provided thorough explanations and content analysis of the trends and dynamics of basic education in Singapore with regards to: curriculum design, teaching methods, special needs and student achievement; pre-service teachers’ training, teachers’ professional development and teachers’ effectiveness; as well as school leadership and community participation. Results indicated that Singapore's basic education has provided a roadmap for success in building competent life-long learners. In conclusion, this study provides evidence that policymakers, planners, and educators from developing countries can take inspiration from Singapore to better their own educational systems and stave off pertinent challenges